2009
DOI: 10.1111/j.1365-2362.2009.02110.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on microRNA 221 / 222 expression in endothelial progenitor cells obtained from patients with coronary artery disease

Abstract: This study demonstrates that LLT with atorvastatin increases EPC numbers and decreases miR-221/222 levels in patients with CAD, possibly contributing to the beneficial effects of LLT with atorvastatin in this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,281 publications
(126 citation statements)
references
References 37 publications
(48 reference statements)
3
123
0
Order By: Relevance
“…In the same way, miR-221 and miR-222 were increased in endothelial progenitor cells from patients with coronary artery disease (CAD) and in those patients, 12 months of treatment with atorvastatin, but not with pravastatin, diminished the expression of miRs-221/222 20 . Those results are in agreement with the reduction of these miRs mediated by statins in our study.…”
Section: Discussionmentioning
confidence: 67%
“…In the same way, miR-221 and miR-222 were increased in endothelial progenitor cells from patients with coronary artery disease (CAD) and in those patients, 12 months of treatment with atorvastatin, but not with pravastatin, diminished the expression of miRs-221/222 20 . Those results are in agreement with the reduction of these miRs mediated by statins in our study.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, a study from Minami et al, suggests the physiological role of miR-221/222 is closely linked to the proliferation of endothelial cells. It was shown that levels of miR-221/222 were significantly higher in the CAD group than in the non-CAD group and levels of miR-221/222 were weakly negatively correlated with Endothelial progenitor cells (EPCs) number in the CAD group (Minami et al, 2009). Collectively, these reports suggest miR-221/222 play an antiangiogenic role in vitro, although the in vivo functions are undetermined.…”
Section: Individual Mirnas In Endothelial Cell Biologymentioning
confidence: 67%
“…A main role for miRNA-221/222 in endothelial therapeutic applications in humans has also been proposed [128]. In fact, recent work demonstrate that miRNA-221 is regulated by hyperglycemia in HUVEC cells, and lipid-lowering therapies (LLT) with atorvastatin increases EPC numbers and decreases miRNA-221/222 levels in patients with coronary artery disease [129,130].…”
Section: The Mirna 221mentioning
confidence: 99%